Minyak Atsiri Kulit Jeruk Sebagai Bahan Obat Hirup Infeksi Saluran Pernapasan Akut (Ispa): Seleksi dan Organoleptik Prototipe Produknya - Fadilah, Nisa Lelita; Monica, Mella; Sigiro, Ria Heni; Batubara, Irmanida (Al-Kimia, 2021)
Acute Respiratory Infection (ARI) is an acute inflammation of the upper or lower respiratory tract caused by bacterial, viral, fungal and other parasitic infections. Lemon peels have been reported to contain beneficial compounds such as phenolic compounds and flavonoids. Flavonoids have been reported to have antioxidant, antibacterial, antiviral, anti-inflammatory, anti-allergic and anticancer activities. The review was conducted to select the orange peel from the best type of orange that can be used as an inhaler for people with ARI. National and international journals were selected based on the keywords citrus peel, antibacterial and antiviral. The chemical components reported in the essential oils of various citrus peels were determined and correlated with their related activity as antibacterial and antiviral. This systematic review shows that compounds that have the potential as antimicrobial, antibacterial and antiviral are flavonoids and limonina, these compounds are widely contained in the essential oil of lemon peel. The conclusion of the review shows that lemon peel essential oil has the potential as a raw material for anti-ARI drugs.